Analysis of Students' Mathematical Connection Skills in Solving High-Order Thinking Skills Problems if Flat- Sided Space Building - Desmira Maharani; Kartini Kartini; Yenita Roza (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2025)
Mathematical connection skills are essential for solving Higher-Order Thinking Skills (HOTS) problem, yet Indonesian students struggle to link concepts across contexts. This study investigates how junior high school students apply these skilss in flat-sided space geometry, addressing gaps in contextual and interdisciplinary problem solving. A descriptive qualitative approach was employed with 18 Class VIII students at MTs Daarun Nahdhah Bangkinang. Data were collected through a validated essay text (expert judgment: k=0.82) measuring three indicators: (1) inter-mathematical concept connection, (2) mathematics to other fields applications, and (3) real world problem solving. Responses were scored using a rubric (0-4 scale) and analyzed thematically by ability level(high/medium/low). Only 28% of students excelled in connecting mathematical concept (indicator 1), while 22% performed well in interdisciplinary applications (indocator 2). Real world problem solving (indicator 3) showed the lowest mastery (11%). High ability students demonstrated coherent relational understanding, whereas medium/low ability students relied on rote memorization or made calculation error. The finding highlight critical gaps in students ability to contextualize mathematics, emphasizing the need for scaffolding in curriculum design. Implications suggest integrating real world examples and interdisciplinary tasks to strengthen HOTS based connection.